Pengembangan Multimedia Interaktif berbasis Website pada Mata Pelajaran Adobe Photoshop untuk Kelas X Program Keahlian Multimedia di SMK Negeri 4 Malang - Moh. Septian Al Fikri; Retno Indah Rokhmawati; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
There are several majors in SMK 4 Negeri Malang, for example Multimedia. When learners are not given learning media other than power points, because the supervisor uses the lecture method to use media in the form of PowerPoint. The solution that can be used to deal with problems is to build an Interactive Multimedia learning media. Through Interactive Multimedia can motivate and attract student attention about the material presented. Development of Interactive Multimedia can be done using Notepad ++ software as a text editor and Adobe Premiere Pro 2017 for editing video material. Data collection techniques used are observation, question and answer with a guide, questionnaire and test giving. The results of the validation test for material experts and media experts are that the learning media designed in the form of Interactive Multimedia are valid and appropriate for the learning process with an average percentage of material and learning experts at 93.3% for the material aspects, and 87.5% for the learning aspect. Which means the learning media is very good. The percentage of the validation test of the media expert is equal to.62.2% where the media has been good. The results of the pre-test carried out by 36 students averaged 76.27 and the average post-test was 83.3. T-test results obtained a significance value smaller than 0.05 of 0,000. Student pre-test and post-test results also gave a significant increase in grades. It can be concluded that Interactive Multimedia is effectively used for the learning process.